Study of the biodegradation of composite materials reinforced with natural resources recovered from industrial areas - BELLILI, Nadira (Biopolymer Applications Journal, 2023)
The aim of our work is to contribute to the search for solutions to the problem linked to environmental pollution by plastic materials and lignocellulosic waste. Composites based on polyvinyl chloride/olive pomace flour (PVC/FGO) with 20% fiber content were prepared. The lack of compatibility between plant fibers and some polymers is due to the hydrophilic nature of plant fibers and the more hydrophobic nature of the matrix. This incompatibility causes poor dispersion of the fibers and the formation of a heterogeneous material whose overall mechanical properties are not satisfactory. In order to improve adhesion at the fiber/matrix interface, the fibers were modified by gamma irradiation. To complete this work, it is essential to carry out an in-depth study of the biodegradation of the materials produced. The PVC/FGO composites were subjected underground under environmental conditions. The changes induced by the exposure of composite materials to biodegradation were evaluated by optical microscopy and the measurement of mass loss